The Use of Online Media “alefbata.com” in Improving Arabic Listening Skills: Experimental Study - Ubaidillah Ubaidillah; Fanni Izzatul Millah; Neli Sapitri (Universitas Islam Negeri Palangka Raya, 2024)
Teachers often overlook listening skills during the learning process, resulting in students needing help with this core skill for second language acquisition. Observations have shown issues with Arabic listening skills and a need for more utilization of online media in the learning process. Thus, this study aims to implement the online media website alefbata.com to enhance the Arabic listening skills of students in one of the MTs in Pandeglang Banten. The researchers employed experimental methods, including observation instruments, interviews, pretests, and post-tests, to collect data and determine the effectiveness of alefbata.com in improving listening skills. After analyzing the data, it is evident that online media is efficacious in improving Arabic listening skills. The post-test results support the claim that students' listening ability increased after exposure to online media. The experimental class had an average score of 82.78, significantly higher than the control class's average score of 42.41, with a difference of 40.37. Therefore, there was an increase in students' listening skills after processing it using online media in teaching activities for class VII B Mts in Pandeglang.